Examining the rate of vegetation diversity under abandoned skid trails in Peninsular Malaysia forest - Razali, Noraimy; Kamarudin, Norizah; Ismail, Mohd Hasmadi (Scienceweb Publishing, 2014)
Skidding operations have been widely reported as a source of negative impact on soils and damage to vegetation. The diversity of species regenerated includes species richness, dominancy and evenness index that were discovered within abandoned skid trails after timber harvesting operations were enumerated in this study. Three classes of habitat were sampled: skid trail tracks, edges of skid trail and adjacent forests. Shannon’s diversity index shows different indices are recorded for seedlings and saplings within the three habitats studied. Some seedlings were found to exist in all three habitats studied, and fewer or even none of the saplings were found within skid trail tracks; on the contrary, many saplings were found within edges and adjacent forests. While no dipterocarp species was found within skid trail tracks, Shorea sp. was found within edges and adjacent forests, and Hopea pubescens was only found within adjacent forests. The results show that there are different regeneration rates among the three different habitats depending on the size of gaps created during skidding operations. High regeneration rate was found to occur within edges habitat since it is more suitable compared with the other two habitats.